Implementation of Cognitive, Affective, Psychomotor Aspect Assessment Case Study at SDN Ngembung Cerme Gresik - As rori; Moch Charis Hidayat (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Research on the performance assessment of prayer practice which includes three aspects, namely cognitive, affective and psychomotor in SDN Ngembung Cerme Gresik, because with this assessment can see students 'thinking ability in gaining knowledge (cognitive ability), assessing students' attitudes during prayer practice (affective ability), and assess students' skills in using equipment (psychomotor skills). The material to be used is Practicing Fardhu Prayer, because according to the researcher (as a PAI teacher), that this material has never been carried out in a thorough assessment (cognitive, affective and psychomotor) for the practice of prayer, other than that this material is material that is considered difficult by the student. In general, students are not fully able to understand the procedures of the Fardhu Prayer if only explained to the extent of theory without any direct practice.In this study using a qualitative descriptive approach. Research whose data in the form of words, derived from interviews, report notes, documents, etc.) or research in which prioritizes the analysis of an event or process as it exists in the natural environment to obtain a deep meaning of the nature of the process . Data analysis includes student score data and student response data.Based on the results of research and discussion of performance appraisal on the subject matter Prayer Practices Practicing Fardhu Prayers in class VI SDN Ngembung Cerme Gresik  it can be concluded that: (1) The results of the performance evaluation of students in class VI are generally well implemented. The results of performance appraisal on the cognitive aspect are 34.1% received the highly successful category and 65.9% got the successful category. The results of the performance evaluation on the psychomotor aspect are 18.2% got the very successful category 70.4% got the successful category and 11.4% got the less successful category. The results of the performance appraisal on the affective aspect are 20.5% got the very successful category, 68.2% got the successful category and 11.3% got the less successful category, (2) From the results of the student response questionnaire it is known that students can be motivated to have competence in PAI lessons with learning using performance appraisal. Besides that students feel happy and feel the many benefits that can be obtained from learning using performance assessment. Keywords: Assessment, Cognitive, Affective, Psychomotor.